Multiple coronary and cerebral aneurysms in a patient with chronic thromboangiitis. Issue 5 (November 2018) - Yamamoto, Masaki; Nakashima, Junko; Iguchi, Mitsuko; Tashiro, Miwa; Noguchi, Tatsuya; Hiroi, Makoto; Inoue, Keiji; Hanazaki, Kazuhiro; Orihashi, Kazumasa
Abstract: A 73-year-old man had multiple coronary aneurysms that resulted in acute myocardial infarction on the day before surgery for cerebral aneurysms. Emergent coronary angiography revealed that the lesion that caused the myocardial infarction was a distal left circumflex artery, and two huge coronary aneurysms were also found in the left circumflex artery. A two-stage treatment strategy was planned, including coronary aneurysm surgery, followed by cerebral aneurysm surgery. He underwent coronary artery aneurysmorrhaphy with closure of the ostia of the afferent and efferent arteries, and coronary artery bypass grafting with a saphenous vein graft applied to the left circumflex artery. The pathological findings suggested chronic thromboangiitis, as the inflammatory cells were observed to have infiltrated the coronary artery wall. The tissue remodeling of the aneurysmal wall indicated a positive response to tenascin C. We report a case of multiple coronary aneurysms, focusing on the pathological findings. <Learning objective: Only few reports have described coronary aneurysms related to inflammatory, atherosclerotic, and connective tissue diseases. This report describes the simultaneous occurrence of coronary and cerebral artery aneurysms, focusing on the histopathological findings. The patient's histopathological examination revealed a positive response to tenascin C, which suggested tissue remodeling of the aneurysmal wall and chronic thromboangiitis.>